2011
DOI: 10.1074/jbc.m110.139915
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagosome Formation by the Benzoporphyrin Derivative Verteporfin

Abstract: Autophagy enables cells to degrade and recycle cytoplasmic materials both as a housekeeping mechanism and in response to extracellular stress such as nutrient deprivation. Recent studies indicate that autophagy also functions as a protective mechanism in response to several cancer therapy agents, making it a prospective therapeutic target. Few pharmacological inhibitors suitable for testing the therapeutic potential of autophagy inhibition in vivo are known. An automated microscopy assay was used to screen >3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 44 publications
2
113
1
Order By: Relevance
“…The photosensitizer used in these studies was found to inhibit autophagosome formation at a 10 ÎŒM concentration in the dark. 19 Consistent with studies involving the KD line, photosensitization with the higher BPD level, followed by irradiation with a reduced light flux eliminated the shoulder on the dose-response curve associated with the cytoprotective effect of autophagy. Use of high-dose BPD could potentiate PDT efficacy where autophagy offers protection from photokilling, if tumor selectivity is not thereby lost.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The photosensitizer used in these studies was found to inhibit autophagosome formation at a 10 ÎŒM concentration in the dark. 19 Consistent with studies involving the KD line, photosensitization with the higher BPD level, followed by irradiation with a reduced light flux eliminated the shoulder on the dose-response curve associated with the cytoprotective effect of autophagy. Use of high-dose BPD could potentiate PDT efficacy where autophagy offers protection from photokilling, if tumor selectivity is not thereby lost.…”
Section: Discussionsupporting
confidence: 68%
“…A recent report described the unexpected ability of BPD (in the dark) to antagonize autophagosome formation after starvation or other stimuli. 19 This inhibitory effect was not observed until the BPD concentration was ≄10 ÎŒM. In studies reported above, the concentration of BPD never exceeded 1 ÎŒM.…”
mentioning
confidence: 98%
“…81 The authors suggested that this potentiation of PDT with higher concentrations of BPD is due to inhibition of autophagy because autophagosomes that are formed as a result of an autophagy-mediated cellular response can be inhibited by 10 ÎŒM BPD. 99 It has been shown in several instances that autophagy can be cytoprotective against phototoxicity. 81,100 However, biological variability between cell lines and disease models significantly impacts overall PDT efficacy for many reasons including differential PS uptake, PS localization, and differences in the photochemical and photophysical mechanisms lead to cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…As modulation of autophagy represents a novel approach for enhancing the therapeutic efficacies of cancer therapy, research efforts have been put forth to identify agents that induce or inhibit autophagy. Several FDA (Food and Drug Administration)-approved drugs have been identified as inducers (for example, rapamycin, fluspirilene, trifluoperazine, pimozide, niguldipine, nicardipine and amiodarone, loperamide) or inhibitors (for example, chloroquine, hydroxychloroquine, verteporfin) of autophagy (Zhang et al, 2007;Donohue et al, 2011). The toxicological and pharmacokinetic profiles of these agents are well established and, therefore, these agents can be easily incorporated into existing regiments of cancer therapy.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%